AN ANALYSIS ON SUBTITLING STRATEGIES OF ROMEO AND JULIET MOVIE - Endang Dwi Hastuti (Register Journal, 2015)
The focus of this research is to identify the subtitling strategies applied in the subtitling of Romeo and Juliet movie. This research belongs to descriptive qualitative research along with purposive sampling techniques. The objects of the research are English sentences spoken by the actors and actress in Romeo and Juliet movie as a source text (ST) and its Indonesian subtitling as a target text (TT).